ANALISIS PENGARUH KUALITAS PRODUK, HARGA, PROMOSI, DAN KEUNGGULAN KOMPETITIF TERHADAP KEPUTUSAN PEMBELIAN MOBIL HYUNDAI (Studi Kasus : Showroom Hyundai Pondok Indah) - Dayat Hidayat; Ugeng Budi Haryoko; Edi Sukarjono (Inovasi, 2014)
COMPETITIVE ADVANTAGES OF DECISION TO PURCHASE CAR HYUNDAI (Case Study: Hyundai Showroom Pondok Indah). This study aims to determine the effect of Product Quality, Price, Promotion, and Competitive Advantage together against the car buying decision using explanatory survey. The respondents are a number of car buyers Hyundai totaling 96 people, were selected, with a purposive sampling technique. Results showed that: (1) There is a significant influence between product quality with Hyundai car purchasing decisions by 48.2%. (2) There is a significant relationship between the price of the Hyundai car purchasing decisions by 57.6%. (3) There is a significant relationship between the promotion of the Hyundai car purchasing decisions by 54.4%. (4) There is a significant relationship between competitive advantage with Hyundai car purchasing decisions by 58.3%. (5) Simultaneously, a significant difference between the quality of the product, price, promotion, and competitive advantage at 70.4%.This study concluded that the decision on the purchase of cars Hyundai Hyundai car showroom Pondok Indah influenced by the quality of the product, price, promotion, and competitive advantage Keywords: quality of product, price, promotion, competitive advantage, and purchasing decisions.